FACTORS ASSOCIATED WITH POST PARTUM HEMORRHAGE - Sarina Ali (International Journal Of Health Science, 2022)
Postpartum hemorrhage is bleeding or blood loss of more than 500cc that occurs after the child is born either before, during or after the birth of the placenta. Several risk factors increase the incidence of postpartum hemorrhage, namely prolonged labour, more than one baby in the fetus, episiotomy (the act of opening the birth canal by providing a cut around the birth canal), large babies of more than 4000 grams, history of bleeding, anemia during pregnancy, age too late pregnancy.Purpose: Research to determine the factors associated with the incidence of postpartum hemorrhage.Research method: This research is a quantitative study with a cross sectional approach. The sample was part of post partum mothers from the medical records of Regional public hospital H.Padjonga Dg.Ngalle, totaling 40 people. The sampling technique is accidental sampling. The method of data collection in this study was secondary data by opening the register of patients who experienced post partum bleeding at the Regional public hospital H. Padjonga Dg. Ngalle, Takalar Regency. After that retrieve the data and select complete data based on the specified criteria. Data were analyzed using chi-square.